Our Common Home: Eastern Europe / Central Europe / Post-Communist Europe as Signifiers of Cultural-Political Geographies and Identities - Stavreva, Kirilka; Sokolova, Boika; Pikli, Natália; Wild, Jana (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The article discusses the historical mutability and political connotations of the geographical signifiers Eastern and Central Europe, and the chronotope Post-Soviet / Post-Communist Europe. It considers the tensions present in these denominations, arguing for the need to defamiliarize and re-define them. Three major sections survey the circumstances that shaped the referential and connotative values of the terms from the Enlightenment to the era of European integration. The article notes commonalities in the defining experiences of the countries in the east of Europe: their emergence from the ruins of former empires (Habsburg, Russian, Ottoman) and of the Soviet bloc. It considers whether the spatial terms have been developed from within or imposed from the outside, and discusses how they have perpetuated stereotypes of the region under consideration and its people(s) and generated enduring cultural myths. It concludes by proposing terms that recoup the cultural significance of the region—East-Central Europe, its close correlative East-Centre Europe, the neologism Europeast—and by alerting scholars working on transnational Shakespeare adaptations to the importance of recontextualizing research in individual national traditions as part of a larger investigation of the mutual translatability of shared experiences. The publication of the article was supported by the International Visegrad Fund, project no. 22210007, titled “Crossing Borders with Shakespeare since 1945: Central and Eastern European Roots and Routes.” The project is co-financed by the Governments of the Czechia, Hungary, Poland and Slovakia through Visegrad Grants. The mission of the Fund is to advance ideas for sustainable regional cooperation in Central Europe.